PENERAPAN GAMIFICATION MATEMATIKA BERBASIS ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X-3 MAN 2 PANDEGLANG - Indriani, Arina Nur (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to determine the effect of implementing Artificial Intelligence-Based Mathematics Gamification on the learning motivation of 10th-grade students at MAN 2 Pandeglang. The study employed a quantitative approach with a quasi-experimental method and a One Group Pretest-Posttest Design. The sample consisted of 28 10th-grade students selected using a purposive sampling technique. The research instrument was a learning motivation questionnaire designed based on Uno's learning motivation indicators: desire to succeed, drive to learn, hope for the future, appreciation for learning, engaging learning activities, and a conducive learning environment. Data were collected through pretests and posttests, then analyzed using descriptive statistics and a Paired Sample t-test. The results showed that the average student learning motivation score increased from 68.42 in the pretest to 84.76 in the posttest, representing an increase of 16.34 points, or 23.88%. The hypothesis test obtained a significance value of 0.000 (p < 0.05), indicating a significant difference between learning motivation before and after the treatment. Thus, the implementation of Artificial Intelligence-Based Mathematics Gamification has proven effective in increasing the learning motivation of class X-3 students at MAN 2 Pandeglang.